Promoting Scientific Research Activities in Universities in Vietnam in the Fourth Industrial Revolution - Tien Anh, Tran (VNU Journal of Science: Policy and Management Studies; Vol 38 No 1, 2022)
Scientific research is the finding and discovery of the nature of things and the creation of solutions that affect history and transform things according to their intended use. Scientific research is a social activity to satisfy the need to perceive and improve the world. In the context of the fourth industrial revolution, it is necessary to develop appropriate policy systems to promote scientific research in universities, which serve as the cradle of research, by linking the relationships of Universities - Research Institutes – Enterprises. Keywords Scientific research, Universities, The Fourth Industrial Revolution References [1] V. C. Dam, Some Issues of Science and Technology Management in our Country, Scientific and Technical Publisher, 2011, pp. 70 (in Vietnamese). [2] T. Q. Hoc, to Learn More About a Research University, https://vnu.edu.vn/ttsk/?C1657/N7275/de-hieu-hon-ve-mot-dai-hoc-nghien-cuu.htm/, 2009 2009 (in Vietnamese). [3] N. H. Hai, T. T. Anh, The Vietnamese Enterprise’s Technological Capacity in the Context of the 4th Industrial Revolution, VNU Journal of Science: Policy and Management Studies, Vol. 35, No. 3, 2019 (in Vietnamese). [4] OECD, Innovation and Development Agenda, The Relevance of Innovation Systems to Developing Countries, 2010, pp. 43. [5] Z. W. Todorovic, Rod B. McNaughton, Paul Guild, ENTRE-U: An Entrepreneurial Orientation Scale for Universities, 2010. [6] L. Weiming, L. Chunyan, D. Xiaohua, Ten years of Entrepreneurship education in Chinese universities: Evolution, Problems and System building, Chinese Education & Society, Vol. 49, 2016, pp. 198. [7] Y. M. Kalman, A Race to the Bottom: MOOCs and Higher Education Business Models, Open Learning, Vol. 29, No. 1, 2014, pp. 5.